Labour inspection and trade unions: criticism of their interaction and foundations for a collaborative relationship - Mendoza Legoas, Luis (2024)
The relationship between the trade union movement and labour inspection is complex and its observation in the Peruvian context in recent years allows us to deduce certain practical rules about this reality. We are not facing a simple sum of protective efforts over the rights of workers covered by both entities: there are cases in which the real capacity of both actors can be mutually enhanced and sometimes counteracted. Thus, after a legal investigation –which makes use of inductive and jurisprudential methods– and with a wide-open approach to the socioeconomic effects that the intervention of the union and labor inspection have on labor relations, a specific typology is proposed to understand and value these intersections.